Yuddhoparānta : yuddhabandiyoṃ ke sātha - Vīrasiṃha, 1942- (Tirupati Prakāśana, 1983)
On the treatment accorded to the Pakistani prisoners of war in India, following the India-Pakistan Conflict, 1971.